PERCEPATAN PENYELESAIAN PERDA RTRW KABUPATEN INDRAGIRI HILIR SEBAGAI PEDOMAN PENATAAN RUANG - Rezky Kinanda (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2019)
Regional Regulation on Spatial Planning is an important element for each region because it contains binding regulations regarding spatial planning. This binding regulation will seek strict direction and strict limits on regional development. Regions that do not yet have local regulations on RTRW have the potential to experience conflicts, such as the seizure of spatial use areas by several sectors, furthermore each sector wants to be the main focus and become the most considered sector, then exploitation of space becomes uncontrolled because there are no strict rules governing boundaries. It is in the Regional Regulation on Regional Spatial Planning that local governments can get it all. The drafting or completion of the Regional Regulation on Spatial Planning is not an easy thing to achieve in many regions in Indonesia. The proof is that there are still many regions that do not yet have local regulations on RTRW, including Indragiri Hilir Regency. This becomes the grid that Inhil Regency is threatened to get a negative effect from the absence of RTRW regulations. This journal explains the important points why Inhil District needs a Regional Regulation on RTRW. This is also emphasized by the display of adverse effects if the RTRW regulation is not finished by the Inhil Government. This journal will also explain about any obstacles that the Inhil District Government might face in the effort to resolve the RTRW Perda.